Interactive Science Fiction Prototyping in Virtual Worlds: Fundamentals and Applications - Pirker, J.; Guetl, Christian; Weghofer, P.; Feichtner, V. (iJES, 2014)
Science Fiction Prototyping (SFP) is a powerful tool to imagine, explore, and exploit future technologies, science, and environments and it can be a valuable asset for education, multimedia, and research. This article explores SFP in interactive, flexible, immersive, and collaborative settings, which introduced as Interactive Science Fiction Prototyping (ISFP) and allows new forms of experiencing and reflecting on prototypes. We investigate how to integrate the ISFP process into an existing collaborative virtual world platform and outline required integration steps. Furthermore, we discuss different application scenarios for ISFP in educational, artistic, and business domains and conclude with future ideas and challenges to explore modern scientific ideas.